Cellular, Synaptic and Network Effects of Acetylcholine in the Neocortex - Colangelo, Cristina; Shichkova, Polina; Keller, Daniel; Markram, Henry; Ramaswamy, Srikanth (Frontiers in Neural Circuits, 2019)
The neocortex is densely innervated by basal forebrain cholinergic neurons. Long-range axons of cholinergic neurons regulate higher-order cognitive function and dysfunction in the neocortex by releasing acetylcholine (ACh). ACh release dynamically reconfigures neocortical microcircuitry through differential spatiotemporal actions on cell-types and their synaptic connections. At the cellular level, ACh release controls neuronal excitability and firing rate, by hyperpolarizing or depolarizing target neurons. At the synaptic level, ACh impacts transmission dynamics not only by altering the presynaptic probability of release, but also the magnitude of the postsynaptic response. Despite the crucial role of ACh release in physiology and pathology, a comprehensive understanding of the way it regulates the activity of diverse neocortical cell-types and synaptic connections has remained elusive. This review aims to summarize the state-of-the-art anatomical and physiological data to develop a functional map of the cellular, synaptic and microcircuit effects of ACh in the neocortex, and serve as a quantitative reference for those intending to build data-driven computational models on the role of ACh in governing brain states.